Pemanfaatan Instrumen Observasi sebagai Dasar Asesmen Perkembangan Anak Usia Dini - Nunung Suryana Jamin; Annisa Fahmi Mannassai; Sri Indrawati Zakaria (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2025)
Early childhood development assessment is an important process in obtaining a comprehensive picture of a child's growth and development as a basis for planning learning that is appropriate to the child's needs and characteristics. One of the most relevant assessment techniques for early childhood characteristics is observation, because it is carried out naturally through play and learning activities without putting pressure on the child. This article aims to examine the use of observation instruments as a basis for assessing early childhood development and to provide guidance to early childhood educators in conducting appropriate, systematic, and accountable assessments. The method used in this article is a theoretical study that examines the concept of early childhood assessment, assessment principles, and the process of conducting assessments through observation. The observation instruments discussed include daily records, anecdotal records, and children's work records. The results of the study show that the optimal use of observation instruments can help teachers understand children's development holistically, detect children's special needs, and serve as a basis for decision-making in learning planning and curriculum development. Thus, observation instruments play a strategic role in supporting the assessment process of early childhood development to be more meaningful and oriented towards children's needs.